Comparative analysis of MgCl2 in recently developed liquid state rabies vaccine - JAGANNATHAN S; MANI K.R; VIJAYAKUMAR R; RAHUL GANDHI P; VENKATARAMANA K.N (International Journal of Pharma and Bio Sciences, 2011)
Rabies is normally a rapidly fatal neurological disease and to date therapeutic efforts in humans have proved futile except in rare cases in which rabies vaccine was administered prior to the onset of clinical disease. Safe and potent vaccines produced by cell culture techniques are available in developed countries. One of the most elements in the effective control of human rabies is the use of efficacious vaccines. The stabilizers play an important role in the efficacy of vaccines. Our present study highlights the analysis of Magnesium Chloride as a stabilizer in the newly developed vero cell derived rabies vaccine.